Sepsis survivor mice exhibit a behavioral endocrine syndrome with ventral hippocampal dysfunction. (July 2020) - Spencer-Segal, Joanna L.; Singer, Benjamin H.; Laborc, Klaudia; Somayaji, Khyati; Watson, Stanley J.; Standiford, Theodore J.; Akil, Huda
Highlights: Sepsis survivor mice show anxiety- and depressive-like behavior long after resolution of their acute illness. Sepsis survivor mice show increased hypothalamic-pituitary-axis reactivity and ventral hippocampus glucocorticoid receptor. Decreased ventral hippocampal activation may underlie the sepsis survivor phenotype. Abstract: Severe acute stressors are known to trigger mood disorders in humans. Sepsis represents one such stressor, and survivors often suffer long term from psychiatric morbidity. We hypothesized that sepsis leads to lasting changes in neural circuits involved in stress integration, altering affective behavior and the stress response. To investigate this hypothesis, sepsis was induced in male C57Bl/6 mice using cecal ligation and puncture (CLP), and control mice underwent sham surgery. Mice recovered from acute illness within 2 weeks, after which they exhibited increased avoidance behavior and behavioral despair compared with sham, with behavioral changes observed more than 5 weeks after recovery. Sepsis survivors also showed evidence of enhanced hypothalamic-pituitary-adrenal (HPA) axis activity, with increased corticosterone after a novel stressor and increased adrenal weight. In the brain, sepsis survivor mice showed decreased stress-induced cfos mRNA and increased glucocorticoid receptor immunoreactivity specifically in the ventral hippocampus, a brain region known to coordinate emotional behavior and HPA axis activity. We conclude that murine sepsis survivors exhibit a behavioral neuroendocrine syndrome of negative affective behavior and HPA axis hyperactivity, which could be explained by ventral hippocampal dysfunction. These findings could contribute to our understanding of the human post-intensive care syndrome.